2020
DOI: 10.1039/d0nj03713c
|View full text |Cite
|
Sign up to set email alerts
|

Role of dissolved oxygen in nitroarene reduction by a heterogeneous silver textile catalyst in water

Abstract: Availability of end-user products, including lifesaving medicines and protection materials, from the pharmaceuticals, agrochemicals, dyes, polymers and corrosion industries mainly rely on sustainable catalytic efficiency towards the reduction of nitroaromatics....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 69 publications
2
2
0
Order By: Relevance
“…In fact, in addition to a known decrease in oxygen solubility with temperature, 53 the DO consumption rate increases with temperature and NaBH 4 concentration. 49,51 Furthermore, the dependence of the 4-NiP reduction rate on the ratio between NaBH 4 and alcohol observed in this study (Fig. 7) is also consistent with the hypothesis that alcohols are responsible for the increase of the current concentration of DO in the reaction mixture.…”
Section: Oxygen Solubilitysupporting
confidence: 89%
See 1 more Smart Citation
“…In fact, in addition to a known decrease in oxygen solubility with temperature, 53 the DO consumption rate increases with temperature and NaBH 4 concentration. 49,51 Furthermore, the dependence of the 4-NiP reduction rate on the ratio between NaBH 4 and alcohol observed in this study (Fig. 7) is also consistent with the hypothesis that alcohols are responsible for the increase of the current concentration of DO in the reaction mixture.…”
Section: Oxygen Solubilitysupporting
confidence: 89%
“…21 However, the existence of the reverse oxidation of 4-AP into 4-NiP by DO in the presence of Ag NPs proposed by Neterina was not confirmed by other studies. 21,51 It was suggested that DO is instead consumed both by oxidizing of the reaction intermediate (4-nitrosophenol), and by re-oxidizing the catalyst surface. 21 The participation of DO in the catalyst surface oxidation seems plausible since Ag NPs indeed have been found to be very reactive toward oxygen in the presence of sodium borohydride.…”
Section: Oxygen Solubilitymentioning
confidence: 99%
“…This feature is similar to what was observed in use of silver for oxidation reactions, such as ethene epoxidation, [67–72] or transformation of cyclohexane to cyclohexanone [73,74,75] . Importance of such oxygen species has also been postulated for other processes, such as nitroarene reduction [76] . Most recently, it was found out that silver may also catalyze dioxygen (O 2 ) reduction, which is of great importance for electrochemical devices [77] …”
Section: Properties Of Silver and Its Compoundssupporting
confidence: 77%
“…[73,74,75] Importance of such oxygen species has also been postulated for other processes, such as nitroarene reduction. [76] Most recently, it was found out that silver may also catalyze dioxygen (O 2 ) reduction, which is of great importance for electrochemical devices. [77] A beautiful theoretical screening of diverse metals surfaces activity in dihydrogen splitting has involved silver; [78] however, application of silver-terminated sub-surface alloys in this and other elemental processes remains to be studied.…”
Section: Elemental Silver In Catalysismentioning
confidence: 99%